Evaluating the significance of hypoglycemia in promoting insulin induced hypertension by using a glucose clamp model - Prathipati, Priyanka; Jackson, Debra; Jackson, Keith (International Journal of Medicine, 2017)
Background: Hypoglycemia unawareness is a detrimental risk factor in diabetic patients leading to serious complications if left untreated. Previous studies from our group determined that recurrent insulin induced hypoglycemia (RIIH) promotes hypertension.Objective: We hypothesize that RIIH not insulin by itself is the source of hypertension and end organ damage in diabetic patients.Methods: Male Sprague-Dawley-rats (200-250g, n=18) were provided with glucose food (125g glucose/kg body weight) and glucose water (0.1g glucose/100g body weight/ml). They were treated with subcutaneous insulin injections (7U/Kg) and blood glucose was monitored intermittently. Daily blood pressure was measured using the tail cuff method. Interstitial samples of ATP and angiotensinII (AngII) were collected by renal microdialysis and analyzed using luciferin-luciferase bioluminescent assay and EIA respectively. Reactive oxygen and nitrogen species in hearts and kidneys were analyzed using Electron Paramagnetic Resonance Spectroscopy (EPR).Results: Renal interstitial ATP levels increased from 90.2± 4.7ng/µl to 99.6± 8.7ng/µl (not significant) and AngII from 0.15± 0.02ng/ml to 0.13± 0.05ng/ml (not significant) from day 0 to 14. There was no significant change in mean arterial pressure (121.3 ± 1.4 mmHg on day 0 to 127.8 ± 1.4mmHg on day 14). Oxidative stress was reduced compared to RIIH model, which was evident from the EPR spectra.Conclusion: We demonstrated that hypertension induced end organ damage in diabetics is due to insulin induced hypoglycemia not insulin alone (by itself).